Nutritional characterization of Gliricidia sepium in a saline and high drought ecosystem of the Cauto river basin, Cuba - La O, Orestes (2018)
An experimental sequence with Gliricidia sepium forage was carried out, from a saline and high drought ecosystem of the Cauto river basin, in Granma, Cuba, to determine the chemical composition, in situ effective ruminal degradability (ED) of dry matter (DM) and in vitro apparent and true digestibility of DM, organic matter, neutral detergent fiber and acid detergent fiber using the Daysi @ procedure. For the study of in situ degradability, times of 6, 12, 24, 36, 48 and 72 h were used. In the contents of the chemical composition values of 24.79, 36.32, 19.51, 16.81, 0.16 and 18.74 % were found for crude protein, neutral detergent fiber, acid detergent fiber, hemicellulose, lignin and cellulose, respectively. The kinetic degradation performance was characterized by an increase in the dynamics disappearance of the dry matter with the incubation time in the rumen, while in the effective ruminal degradability of DM values between 63.1 and 67.6 % were obtained for different constants of ruminal replacement. The fit of the in situ ruminal degradability data to the proposed model, P = a + b (1 - e-ct), showed R2 higher to 97.00. The estimates of apparent digestibility of dry matter, organic matter, neutral detergent fiber and acid detergent fiber maintained values of 73.57, 64.25, 26.72 and 14.35 % respectively, much lower than true digestibilities, with 17.88, 67.14, 27.93 and 15.00 % for these same constituents, respectively. The results of the analysis of the chemical composition, in situ ruminal degradability of the dry matter and in vitro apparent and true digestibility of the dry matter, organic matter, neutral detergent fiber and acid detergent fiber of Gliricidia sepium show its high nutritional value for ruminants in the region. However, physiological studies that relates the cut frequency, degree of use of nutrients by the animal and effect of some secondary metabolites on the physiological and productive responses of the animals when intakes the plants in these edaphoclimatic conditions are required.